Prognostic Indicators in Patients with Intracerebral Hematoma in an urban clinical setting of a resource limited Country - Atakla, Hugues Ghislain; Barry, Fatoumata Lounceny; Noudohounsi, Mahugnon Maurel Ulrich Dénis; Ofosu, Benjamin Bekoe; Sulemana, Ummi Sulaimi; Houinato, Dismand Stephan (Nepal Journal of Neuroscience, 2021)
Context and Objective: Hemorrhagic Cerebrovascular Accidents represent 10 to 15% of all strokes and are often related to the spontaneous rupture of small vessels weakened by chronic arterial hypertension or amyloid angiopathy. The aim of this work was to study the prognostic determinants of intracerebral haematomas at the neurology department of Conakry University Hospital. Patients and Method: This was a retrospective analytical study conducted on all patients who were hospitalized with intracerebral hematoma over the 24-month period. Only the records of patients in whom intracerebral hematoma was confirmed by brain imaging were included in this study. Logistic regression (uni-variate and multi-variate) identified prognostic determinants of intracerebral hematoma at p < 0.05. The data were entered using Epi Info software version 7.1.4.0 then analysed using STATA / SE software version 11.2. Results: This study found 21% of cases of intracerebral hematomas during the study period, with a male predominance of 60% and a sex ratio of 1.50. The study was conducted in the presence of a male patient. Hypertension was the cause found in 89.52% of patients; followed by arteriovenous malformations in 6.67% of patients, 2.86% of cases of amyloid angiopathy and 0.95% of unknown cause. Nevertheless, we still recorded 20% of deaths during hospitalization. Conclusion: Previous quality of life and co-morbidities also modify the prognosis and should be taken into account in the prediction of disability and future quality of life of patients with intracerebral haematoma.